Akkermansia muciniphila alleviates cognitive impairment and neuroinflammation induced by blunt chest trauma - Liu, Lin; Wang, Linxiao; Wang, Yanjun; Zhao, Heping; Gao, Xi; Yin, Wen; Xie, Jiangang (Frontiers in Immunology, 2025)
BackgroundBlunt chest trauma, commonly caused by traffic accidents, falls, and violent incidents, results in both direct mechanical injury to the thoracic cavity—leading to increased intrathoracic pressure and vascular rupture—and indirect effects on the central nervous system (CNS), causing extensive damage that severely impacts patient health and quality of life. Akkermansia muciniphila (AKK), a probiotic bacterium inhabiting the gut mucus layer, modulates gut microbiota and metabolites, with potential therapeutic effects on various neurological disorders through the gut-brain axis.MethodsMice were divided into four groups: control, trauma, trauma+PBS, and trauma+AKK. AKK bacterial suspension was administered via gavage for three weeks. Behavioral tests including the OFT, EPM, NORT, and Y-maze were conducted to assess anxiety-like behaviors and cognitive function. Neuroinflammatory markers in the hippocampus were measured using qPCR, immunofluorescence, and Western blot. Gut microbiota and metabolites were analyzed through 16S rRNA sequencing and metabolomics.ResultsMice subjected to blunt chest trauma displayed emotional abnormalities and cognitive deficits. AKK treatment significantly alleviated anxiety-like behaviors and improved cognitive function, reduced pro-inflammatory cytokine levels in the hippocampus, and reshaped gut microbiota composition. AKK also modulated the expression of metabolites linked to neuroinflammation and cognitive function, upregulated BDNF and TrkB, and decreased IBA1, suggesting it enhances cognitive function by modulating neuroinflammation and the BDNF/TrkB signaling pathway.ConclusionsAKK mitigates cognitive impairment and neuroinflammation after blunt chest trauma by modulating gut microbiota and metabolites. Targeting the gut-brain axis may offer new strategies for preventing and treating trauma-induced neurological disorders.